Faktor – Faktor yang Mempengaruhi Keikutsertaan Bidan Praktik Mandiri pada Program Jaminan Kesehatan Nasional di Kota Palangka Raya - Riyanti Riyanti; Seri Wahyuni (Jurnal Surya Medika (JSM), 2017)
Efforts to reduce maternal and infant mortality through various programs including the National Health Insurance program. Midwives play an important role in reducing MMR and IMR, because the midwife is a health worker at the forefront and deal directly with the public, to provide continuous service and complete. This study aims to determine the factors that affect the participation of Independent Midwife Practice On the National Health Insurance Program in the city of Palangkaraya. The approach used in this study was an observational analytic and cross-sectional design. The population in this study are all midwives private practice located in the city of Palangkaraya in 2016. The samples included 105 midwives in private practice. Univariate analysis performed by the frequency distribution for bivariate analysis, age, education, length of practice, knowledge, communication, motivation, cooperation procedure, process claims, the administration process and tariff services using chi-square (x2) and the relationships among several variables were analyzed with multiple logistic regression , The result showed that the factors of education (p = 0.002), duration of practice (p = 0.003), procedure of cooperation (p = 0.000), the process claim (p = 0.042), and administrative processes (p = 0.001) showed a significant effect on the participation of midwives practice of independent Reviewed JKN program. Multiple logistic regression analysis showed that factors of education (OR = 72.23; 95% CI = 2.38 to 218.76), p <0.05, Lama practices (OR = 79.94; 95% CI = 5.22 - 122.45, p <0.05), communications (OR = 97.98; 95% CI = 3.10 to 309.40, p <0.05) and administrative procedures (OR = 56.25; 95% CI = 4.21 to 750.77, p <0.05) simultaneously have a significant influence on the program with the participation of midwives private practices JKN. Conclusion The research results are the effect of education, length of practice, communication, cooperation procedure, process claims, and administrative processes with midwives private practices participation in the program JKN